2011
DOI: 10.3384/ecp110573372
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimization of Urban Planning and Architectural Parameters for Energy use Minimization in Mediterranean Cities

Abstract: This paper reports observations and first experimental results from a field measurement campaign at the neighbourhood/urban scale, which was conducted in July 2010 in Nicosia (Cyprus) under the European Research Project TOPEUM funded by ERA-NET (Urban-Net Call). The ultimate goal of this work is to investigate the influence of urban design and architectural parameters in the resulting urban climate and the resulting energy usage. The field measurement campaign was carried out in the capital city of Cyprus, Nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The average and maximum building height is about 8.1 m and 45.5 m (Shakolas Tower), respectively. The plan area density λ p is about 0.40 (Mouzourides et al, 2014;Neophytou et al, 2011). The width of the streets ranges from 6 m to 10 m, where the aspect ratio of the street canyons (width to height) ranges from 0.5 to 1.…”
Section: Case Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The average and maximum building height is about 8.1 m and 45.5 m (Shakolas Tower), respectively. The plan area density λ p is about 0.40 (Mouzourides et al, 2014;Neophytou et al, 2011). The width of the streets ranges from 6 m to 10 m, where the aspect ratio of the street canyons (width to height) ranges from 0.5 to 1.…”
Section: Case Study Areamentioning
confidence: 99%
“…A series of on-site measurements was conducted in July 2010 inside the area of interest, within the framework of the TOPEUM project (Neophytou et al, 2011). Through an extensive multi-scale and multithemed measurement campaign, data of air temperature, wind speed and surface temperature were collected at different locations inside the case study area for a period of 19 days.…”
Section: Field Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The UHII was found to be above 4 C, while the coastline cites were found to be less affected, with intensities around 1.5 to 3.5 C. The spatio-temporal variation of the UHI intensity for selected heat wave events also indicated that the highest intensities were experienced within the areas of the urban fabric. The value of the UHII in the city of Nicosia is also verified in the work of Neophytou et al 27 Field measurements allowed the investigation of the influence of urban design and architectural parameters in the resulting urban climate and the resulting energy usage in buildings. The surface temperature of the building materials not only showed the impact of the building materials on the intensity of the UHII but it was also concluded that the contribution of thermal radiation, as well as of the anthropogenic emissions in the street canyons led to important temperature increases within the urban fabric of the city.…”
Section: The Uhi Phenomenon In Cyprusmentioning
confidence: 66%